Homerycka psyche jako potoczna kategoria ducha zmarłego - Fajler, Monika (Folia Philosophica, 2018)
The article presents an interpretation of Homeric psyche alternative to the one existing in literature on the subject, where it used to be presented as a soul-breath which gives life to a human being. The interpretation presented here, depicts psyche as a common, pre-reflexive idea of a phantom-spirit, popular in the European culture, being the medium of the universal anthropological convictions. This understanding of psyche, ignored by the examiners of Homer, is in the author’s opinion the basic meaning of psyche arising directly from the texts of Homer’s poems.